ANALISIS KELAYAKAN INVESTASI PADA USAHA KECIL MENENGAH DENGAN PENDEKATAN PAYBACK PERIOD DAN PROFITABILITY INDEKS (STUDI KASUS 3 USAHA COUNTER HANDPHONE) DI KECAMATAN JAMBI SELATAN DAERAH THEHOK JAMBI - Arna Suryani (Universitas Batanghari Jambi, 2010)
Principally, several enterprises undergo effort ( trade ) to want their works go forward and go on expanding. In the research that becomes the object of investigation is three counters handphone, that is, eughty three Cell, Mitto Cell, Hokky Cell, which the company has the Average Small Trade aspectssuch as communication within its activities sell a kind of the communicative products as new handphone, pulse physically and electrically, the physic type of the infrastructure facilities handphone such as : Chasing Handphone, Battery, Handphone Case, Headset, Etc.In this research, is used the secondary data, the investigation method is used by descriptive quantitative. There is also data collection methods practiced with two system, that is : library research and location survey. And then, the usage of analysis instruments is the approach concern with PayBack Period ( PBP ) and Profitability Index (PI).Result of the investigation has found in this research concern with PayBack Period for 2005-2009 is : counter handphone eighty three Cell has PayBack Period one of them is one year four months and counter handphone Mitto Cell PayBack Period was obtained one year three months and finally the counter handphone Hokky Cell PayBack Period was obtained one year three months.Thus, it is explanation above can be inferred that PayBack Period obtained or produced come from the income cash stream ( proceeds ) and capital outlays, so that can be identified by payback period of each counter handphone.Keyword : Payback Period, Profitability Indeks